Efficiency and Toxicity of Ruxolitinib as a Salvage Treatment for Steroid-Refractory Chronic Graft-Versus-Host Disease - Wang, Dong; Liu, Yin; Lai, Xiaoxuan; Chen, Jia; Cheng, Qiao; Ma, Xiao; Lin, Zhihong; Wu, Depei; Xu, Yang (Frontiers in Immunology, 2021)
Graft-versus-host disease (GVHD), especially steroid-refractory GVHD, remains a life-threatening complication after hematopoietic stem cell transplantation (HSCT). The effect of the JAK1/2 kinase inhibitor ruxolitinib on treating steroid-refractory acute GVHD has been verified by the REACH1/2 study; however, its safety and efficacy in patients with steroid-refractory chronic GVHD (SR-cGVHD) remain unclear. In this retrospective study, 70 patients received ruxolitinib as a salvage therapy for SR-cGVHD. Twenty-four weeks after ruxolitinib treatment, the overall response rate (ORR) was 74.3% (52/70), including 34 patients who achieved complete remission (CR) and 18 who achieved partial remission (PR). The main adverse event was cytopenia, which occurred in 51.4% (36/70) of patients. After ruxolitinib treatment, the percentage of CD4 cells increased from 18.20% to 23.22% (P<0.001), while the percentages of NK (CD16+CD56+) cells and regulatory T cells (CD4+CD127±CD25+) decreased (P<0.001, P<0.001). Among the B cell subsets, the proportion of total B cells approximately tripled from 3.69% to 11.16% (P<0.001). Moreover, we observed a significant increase in IL-10 levels after ruxolitinib treatment (P=0.025) and a remarkable decrease in levels of suppression of tumorigenicity 2 (ST2) from 229.90 ng/ml to 72.65 ng/ml. The median follow-up after the initiation of ruxolitinib treatment was 401 (6-1076) days. The estimated one-year overall survival rate of the whole group was 66.0% (54.4–77.6%, 95% CI), and the one-year overall survival rate of patients with mild and moderate cGVHD was 69.6% (57.4–81.8%, 95% CI), which was better than that of patients with severe cGVHD (31.3%, 0.0–66.2%, 95% CI) (P=0.002). Patients who achieved a CR and PR achieved better survival outcomes (84.5%, 73.9–95.1%, 95% CI) than those who showed NR to ruxolitinib treatments (16.7%, 0–34.3%, 95% CI) (P<0.001). At the final follow-up, cGVHD relapse occurred in six patients after they reduced or continued their ruxolitinib doses. Collectively, our results suggest that ruxolitinib is potentially a safe and effective treatment for SR-cGVHD.